Animal - Burnie, David (Dorling Kindersley, 2017)
With more than 1 million copies sold, this updated and revised celebration of the animal kingdom features photos and descriptions of over 2,000 species and habitats. Bringing animals, habitats, and up-to-date research to life for readers around the world, Animal explores the creatures that have fascinated and inspired humans for years, from intrepid Emperor penguins to fierce Siberian tigers, to the very intelligent and highly communicative humpback whale. This updated edition introduces the olinguito, the adorable, recently discovered mammal that looks like a cross between a cat and a teddy bear, and the Skywalker gibbon found in the tropical forests of Yunnan Province in southwest China and Myanmar.